“Critical Media Literacies for 21st Century Educators”: Introducing Critical Literacies to Indonesian Prospective Teachers of English - Subekti, Adaninggar Septi (Universitas Galuh, 2024)
This community service activity was conducted in the form of a public lecture on introducing principles of critical media literacies to learners studying at the English Language Education Study Programme of Universitas Sarjanawiyata Tamansiswa (UST), Yogyakarta. The public lecture was conducted at the Faculty of Teachers' Training and Education and was attended by as many as 37 learner participants from different semesters. Among the key contents of the session, the facilitator raised the participants' awareness that texts are never neutral. They are made by someone, somewhere, for some reason. They are created from a particular perspective to tell particular messages. The participants were also facilitated to realise that various media around them such as movies, TV series, news, and advertisements are also ‘texts’ that are not free from the influences of the authors behind them. By the end of the lecture, as seen from the question-and-answer session, it can be seen that the participants have been successfully facilitated to have a certain degree of critical media literacies. Despite the possible limitations, this community service activity could pave the way for more endeavours to facilitate prospective teachers to be critically literate, and able to facilitate their future students to be able to do so as well in the future.